On the Commitment Needs of Partially Naive Agents - Pan Liu; Torben M. Andersen; Joydeep Bhattacharya (Institute of Labor Economics (IZA), 2020)
Time-inconsistent, present-biased agents may hold commitment assets hoping to keep their current and future present bias in check. Paternalistic governments, in an effort to help such people, routinely offer commitment machinery such as restrictions (or bans) on early withdrawals from defined-contribution, retirement schemes. The larger literature on low uptake of commitment assets recognizes a trade- off: while use of commitment technologies thwarts deviation from pre-selected paths, they, nevertheless, limit flexibility of future selves to respond to unanticipated, consumption shocks. This paper rules out consumption or income shocks by design and yet uncovers a similar trade-off in a world where agents are uncertain but hold beliefs, possibly incorrect, about the present-biasedness of future selves. It shows how fully sophisticated agents — those with correct beliefs about the present-bias of future selves — are happier when the government offers tighter commitment; this is not necessarily so, for the partially naive. Indeed, the latter may be happier than their fully sophisticated counterparts if the government's commitment machinery is slack.
Keywords: D1; D14; 330; time-inconsistency; present bias; savings; commitment